The creative process of Brazilian advertising: Motivators and limiting factors in the creative process - Pimenta Braga, Nívea (2018)
This study investigated how advertisers from the creation area of large advertising agencies perceive and characterize their creative process. Thirteen Brazilian professionals were interviewed using semi-structured interviews. Data were analyzed by content analysis. Results indicate that several stages of the creative process overlap, such as the incubation period of one job functioning as the preparation for the next. Motivating factors include pleasure of the act of creating, media visibility and its social reach. Limiting factors include the agencies’ excessive departmentalization, reduced deadlines, and the clients’ subjectivity influencing the advertisement approval.